Method for preparing high-performance lithium-rich manganese-based positive electrode material by controlling oxygen partial pressure
By controlling the oxygen partial pressure in the co-precipitation reaction and adjusting the composition and structure of the precursor of the lithium-rich manganese-based positive electrode material, the problem of unknown oxygen partial pressure regulation in the prior art is solved, and the preparation of high-performance lithium-rich manganese-based positive electrode material is realized.
Patent Information
- Application Number
- CN202510048624.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-04-18
AI Technical Summary
There is a lack of research in the prior art on preparing lithium-rich manganese-based positive electrode precursors by regulating oxygen partial pressure, which leads to unclear mechanism and laws of oxygen partial pressure on the precursors, which seriously hinders the development of lithium-rich materials.
By accurately controlling the oxygen partial pressure in the co-precipitation reaction, adjusting the oxygen partial pressure in the reaction system to 10% to 60%, optimizing the composition and structure of the precursor in the positive electrode material, thereby improving the electrochemical performance.
The fine regulation of the chemical composition, valence state, microstructure and element distribution of the precursor of the lithium-rich manganese-based positive electrode material is achieved, and the specific capacity, cyclic stability and energy density of the material are improved.
Smart Images

Figure CN119841358A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical power sources, and in particular to a method for preparing a high-performance lithium-rich manganese-based positive electrode material by controlling oxygen partial pressure. Background Art
[0002] With the rapid development of electric vehicles, portable electronic devices and energy storage systems, higher requirements are placed on the energy density, cycle stability and safety of lithium-ion batteries. Due to their unique crystal structure and elemental composition, lithium-manganese-rich based cathode materials exhibit unique transition metal redox and anion redox mechanisms, and therefore have extremely high theoretical specific capacity and high voltage platforms, and their energy density is much higher than that of ternary cathode materials and lithium iron phosphate. In addition, lithium-manganese-rich based materials greatly reduce the use of expensive Co and Ni, and the material cost is significantly reduced. Lithium-manganese-rich based materials are considered to be one of the most promising next-generation lithium-ion battery cathode materials with broad market prospects. However, the performance of lithium-manganese-rich based cathode materials depends largely on the preparation process of their precursors.
[0003] In the English literature Controls of oxygen-partial pressure to accelerate the electrochemical activation in Co-free Li-rich layered oxide cathodes, a strategy was proposed to alleviate the separation of Li2MnO3 components by reducing the oxidation state of part of Mn by adjusting the oxygen partial pressure during the heat treatment process, but the specific material composition changes and their effects on the final performance were not explained in the article.
[0004] At present, the main method is to directly modify lithium-rich materials under synthetic conditions to improve the structural stability of the materials, thereby improving their electrochemical performance. However, there is currently no research on preparing lithium-rich manganese-based positive electrode precursors by regulating oxygen partial pressure. The mechanism and law of the effect of oxygen partial pressure on precursors are unclear, which seriously hinders the development of lithium-rich materials. Summary of the invention
[0005] Purpose of the invention: The first purpose of the present invention is to provide a method for preparing high-performance lithium-rich manganese-based positive electrode materials by oxygen partial pressure. This method optimizes the composition and structure of the precursor in the positive electrode material by precisely controlling the oxygen partial pressure in the precursor co-precipitation reaction, thereby improving the electrochemical performance of the positive electrode material.
[0006] Technical solution: The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to the present invention comprises the following steps:
[0007] (1) introducing a nickel-manganese-based mixed sulfate solution and a complexing agent to obtain a solution A and a precipitant solution B into a closed reaction vessel, respectively, and adjusting the oxygen partial pressure in the reaction system to a predetermined range by controlling the ratio of oxygen and non-oxidizing gas;
[0008] (2) performing a coprecipitation reaction to uniformly precipitate metal ions under a controlled oxygen partial pressure environment to form a coprecipitation product;
[0009] (3) Separating the coprecipitated product, washing and drying it, the obtained hydroxide precursor Ni x Mn y M z (OH)2;
[0010] (4) Mixing the hydroxide precursor and the lithium source, and preparing the lithium-rich manganese-based positive electrode material Li by solid phase sintering or molten salt method 1+a [Ni k Mn d M c ]O2;
[0011] The oxygen partial pressure is 10% to 60%.
[0012] Oxygen partial pressure not only affects the precipitation rate of metal ions and the composition of the precipitate, but also directly affects the composition and structure of the precursor. This effect is particularly evident under different oxygen partial pressure conditions.
[0013] In a lower oxygen partial pressure environment, metal ions may be more inclined to form reduced compounds, which may cause changes in the element ratio, valence state, and microstructure in the precursor. For example, some metal ions may form more stable low-valent ions or compounds under reducing conditions, thereby affecting the chemical composition and physical properties of the precursor. In addition, low oxygen partial pressure may also slow down the precipitation rate, making the precursor formation process slower and more controllable, which helps to form a more uniform and dense microstructure.
[0014] Under conditions of excessively high oxygen partial pressure, metal ions may be more easily oxidized to form high-valent ions or compounds. This may cause the chemical composition of the precursor to deviate from expectations or even form undesirable impurity phases. At the same time, high oxygen partial pressure may also accelerate the precipitation rate, making the precursor formation process faster and more uncontrollable, which may cause the precursor's microstructure to become uneven or defective.
[0015] Therefore, by precisely controlling the oxygen partial pressure in the reaction system, it is possible to finely regulate the chemical composition, valence state, microstructure and element distribution of the precursor. This regulation not only helps to improve the electrochemical properties of lithium-rich manganese-based cathode materials, such as increasing specific capacity, improving cycle stability and rate performance.
[0016] More preferably, the oxygen partial pressure is 15-35%.
[0017] The Ni x Mn y M z In (OH)2, 0.2≤x≤0.26, 0.75≤y≤0.8, 0≤z≤0.06, and M is selected from Mg, Al, Ti, Zr, Nb, Mo, Fe, Zn, Na, W, Co, Cr, Y or Cu.
[0018] The Li 1+a [Ni k Mn d M c ]O2, 0.08≤a≤0.26, 0.10≤k≤0.22, 0.45≤d≤0.66, 0≤c≤0.05, and M is selected from Mg, Al, Ti, Zr, Nb, Mo, Fe, Zn, Na, W, Co, Cr, Y or Cu.
[0019] Preferably, in step (1), the precipitant is aqueous ammonia, which is used to stabilize the metal ions in the mixed solution.
[0020] Preferably, in step (1), the non-oxidizing gas is nitrogen.
[0021] Preferably, in step (2), the precipitation reaction temperature is 30-70° C., and the reaction time is 8-12 h.
[0022] Preferably, the precipitant is NaOH, and the pH of the precipitation reaction is 10 to 13.5.
[0023] Preferably, the lithium source is Li2CO3 or LiOH·H2O.
[0024] Preferably, in step (4), the sintering conditions are as follows: a pre-sintering temperature of 450-550° C. for 4-6 hours, and after pre-calcination or directly raising the temperature to 800-900° C. for high-temperature sintering for 10-12 hours.
[0025] Invention mechanism: The present invention uses a sulfate solution to prepare a transition metal hydroxide precursor by a coprecipitation method, and then uses the transition metal hydroxide precursor and an inorganic lithium salt as a lithium source, and adopts a high-temperature solid-phase calcination process to prepare a lithium-rich manganese-based positive electrode material Li 1+a [Ni k Mn d M c]O2. This method effectively regulates the structure and composition of the lithium-rich manganese-based positive electrode precursor by adjusting the ratio of oxygen partial pressure. The oxygen partial pressure affects the precipitation rate of metal ions and the composition of the precipitate, and also directly affects the composition and structure of the precursor, thereby further improving the capacity, cycle stability and energy density of the lithium-rich manganese-based positive electrode material. Therefore, the lithium-rich manganese-based positive electrode precursor is regulated by regulating the oxygen partial pressure, which helps to ultimately achieve a new type of lithium-rich positive electrode material with high energy density and excellent cycle performance.
[0026] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: (1) By adjusting the oxygen partial pressure to control the structure and composition of the precursor, the effective pinning of transition metal ions in the Li layer is achieved. This unique mortise and tenon structure enhances the stability of the material structure, enhances the cycle stability and improves the electrochemical performance; (2) The preparation method adopts a high-temperature solid-phase calcination method by mixing a hydroxide precursor with a lithium source, and does not require complex steps such as water washing and drying. It is low-cost, simple in process, and can be mass-produced. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 XRD pattern of the lithium-rich manganese-based positive electrode material prepared in Example 1;
[0028] Figure 2 XRD pattern of lithium-rich manganese-based positive electrode material prepared in ratio 1;
[0029] Figure 3 This is the XRD pattern of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2;
[0030] Figure 4 The first two charge-discharge curves of the lithium-rich manganese-based positive electrode material prepared in Example 1 in the voltage range of 2.0 to 4.8 V (0.1C 25 mA);
[0031] Figure 5 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Example 1 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0032] Figure 6 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Example 2 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0033] Figure 7 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Example 3 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0034] Figure 8 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Example 4 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0035] Fig. 9 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Example 5 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0036] Fig.10 The cycle curve of the lithium-rich manganese-based positive electrode material prepared in Ratio 1 in the voltage range of 2.0 to 4.8 V (1C 250 mA);
[0037] Fig.11 This is a cycle curve diagram of the lithium-rich manganese-based positive electrode material prepared in Comparative Example 2 in the voltage range of 2.0 to 4.8 V (1C 250 mA). DETAILED DESCRIPTION
[0038] The technical solution of the present invention is further described below in conjunction with embodiments.
[0039] Example 1
[0040] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0041] (1) 200 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (56 g of nickel sulfate hexahydrate and 106 g of manganese sulfate monohydrate as solvent, 200 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 200 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0042] (2) introducing solution A and precipitant solution B into a closed reaction vessel respectively, and controlling the ratio of oxygen and nitrogen to achieve an oxygen partial pressure of about 25% in the system;
[0043] (3) Under the conditions of constant temperature of 50°C, stirring speed of 500 rpm, pH value of 11.4 and reaction time of 12 h, a coprecipitation reaction was carried out to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.3g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450℃ at a heating rate of 5℃ / min in an air atmosphere in a muffle furnace and kept warm for 6h. It was then heated to 900℃ and sintered at high temperature for 12h. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0044] Example 2
[0045] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0046] (1) 200 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (56 g of nickel sulfate hexahydrate and 106 g of manganese sulfate monohydrate as solvent, 200 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 200 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0047] (2) introducing solution A and precipitant solution B into a closed reaction vessel respectively, and controlling the ratio of oxygen and nitrogen to achieve an oxygen partial pressure of about 10% in the system;
[0048] (3) Under the conditions of constant temperature of 50°C, stirring speed of 500 rpm, pH value of 11.4 and reaction time of 12 h, a coprecipitation reaction was carried out to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.3g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450℃ at a heating rate of 5℃ / min in an air atmosphere in a muffle furnace and kept warm for 6h. It was then heated to 850℃ and sintered at high temperature for 12h. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0049] Example 3
[0050] The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0051] (1) 150 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (42 g of nickel sulfate hexahydrate and 80 g of manganese sulfate monohydrate as solvent, 200 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 150 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0052] (2) introducing solution A and precipitant solution B into a sealed reaction vessel respectively, and adjusting the oxygen partial pressure in the reaction system to 35% by controlling the ratio of oxygen and nitrogen;
[0053] (3) A coprecipitation reaction was carried out at a constant temperature of 50°C, a stirring speed of 500 rpm, a pH value of 11.8, and a reaction time of 12 h to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.3g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450℃ at a heating rate of 5℃ / min in an air atmosphere in a muffle furnace and kept warm for 6h. It was then heated to 900℃ and sintered at high temperature for 12h. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0054] Example 4
[0055] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0056] (1) 160 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (43 g of nickel sulfate hexahydrate and 84 g of manganese sulfate monohydrate as solvent, 200 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 160 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0057] (2) introducing solution A and precipitant solution B into a sealed reaction vessel respectively, and adjusting the oxygen partial pressure in the reaction system to 40% by controlling the ratio of oxygen and nitrogen;
[0058] (3) Under the conditions of constant temperature of 50°C, stirring speed of 500 rpm, pH value of 11.8 and reaction time of 12 h, a coprecipitation reaction was carried out to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.3 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 840°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0059] Example 5
[0060] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0061] (1) 170 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (46 g of nickel sulfate hexahydrate and 90 g of manganese sulfate monohydrate as solvent, 170 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 170 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0062] (2) introducing solution A and precipitant solution B into a sealed reaction vessel respectively, and adjusting the oxygen partial pressure in the reaction system to 60% by controlling the ratio of oxygen and nitrogen;
[0063] (3) Under the conditions of constant temperature of 50°C, stirring speed of 500 rpm, pH value of 11.8 and reaction time of 10 h, a coprecipitation reaction was carried out to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.3 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 950°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0064] Example 6
[0065] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0066] (1) 150 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (40 g of nickel sulfate hexahydrate and 80 g of manganese sulfate monohydrate as solvent, 150 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 250 mL of a 4 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0067] (2) introducing solution A and precipitant solution B into a sealed reaction vessel respectively, and adjusting the oxygen partial pressure in the reaction system to 23% by controlling the ratio of oxygen and nitrogen;
[0068] (3) A coprecipitation reaction was carried out at a constant temperature of 50°C, a stirring speed of 500 rpm, a pH value of 11.9, and a reaction time of 12 h to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.4 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 890°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0069] Example 7
[0070] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0071] (1) 250 mL of a 1.0 mol / L nickel-manganese-based mixed sulfate solution (68 g of nickel sulfate hexahydrate and 133 g of manganese sulfate monohydrate as solvent, 250 mL of water as solvent) was mixed with 9 mL of 3.5 mol / L ammonia water to obtain a mixed solution A, and 250 mL of a 4.5 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0072] (2) introducing solution A and precipitant solution B into closed reaction vessels respectively and reacting them under air conditions;
[0073] (3) Under the conditions of constant temperature of 50°C, stirring speed of 500 rpm, pH value of 12.5 and reaction time of 12 h, a coprecipitation reaction was carried out to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.4 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 900°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0074] Example 8
[0075] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.25 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Mn 0.6 ]O2, comprising the following steps:
[0076] (1) 300 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (81 g of nickel sulfate hexahydrate and 159 g of manganese sulfate monohydrate as solvent, 300 mL of water as solvent) was mixed with 9 mL of 4 mol / L ammonia water to obtain a mixed solution A, and 300 mL of a 4 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0077] (2) introducing solution A and precipitant solution B into a sealed reaction vessel respectively, and adjusting the oxygen partial pressure in the reaction system to 70% by controlling the ratio of oxygen and nitrogen;
[0078] (3) A coprecipitation reaction was carried out at a constant temperature of 50°C, a stirring speed of 500 rpm, a pH value of 12.5, and a reaction time of 10 h to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.1 g of LiOH·H2O, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 900°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0079] Example 9
[0080] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.20 Mg 0.05 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.16 Mg 0.04 Mn 0.6 ]O2, comprising the following steps:
[0081] (1) 300 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (81 g of nickel sulfate hexahydrate and 159 g of manganese sulfate monohydrate and 25 g of magnesium sulfate heptahydrate as solvents, 300 mL of water as solvent) was mixed with 9 mL of 4 mol / L ammonia water to obtain a mixed solution A, and 300 mL of a 4 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0082] (2) introducing solution A and precipitant solution B into closed reaction vessels respectively and reacting them under air conditions;
[0083] (3) A coprecipitation reaction was carried out at a constant temperature of 50°C, a stirring speed of 500 rpm, a pH value of 12.3, and a reaction time of 10 h to form precursor particles. 2.1 g of Ni 0.25 Mn 0.75 The (OH)2 precursor was mixed with 1.4 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 900°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0084] Example 10
[0085] The method for controlling oxygen partial pressure to prepare high-performance lithium-rich manganese-based positive electrode materials of the present invention, wherein the precursor molecular formula is Ni 0.20 Al 0.05 Mn 0.75 (OH)2, the molecular formula of the positive electrode material is Li[Li 0.2 Ni 0.2 Al 0.04 Mn 0.6 ]O2, comprising the following steps:
[0086] (1) 300 mL of a 2.0 mol / L nickel-manganese-based mixed sulfate solution (81 g of nickel sulfate hexahydrate and 159 g of manganese sulfate monohydrate as solvents and 38 g of aluminum sulfate 18hydrate as solvents, and 300 mL of water as solvent) was mixed with 9 mL of 4 mol / L ammonia water to obtain a mixed solution A, and 300 mL of a 4 mol / L sodium hydroxide solution was prepared as a precipitant solution B;
[0087] (2) introducing solution A and precipitant solution B into closed reaction vessels respectively and reacting them under air conditions;
[0088] (3) A coprecipitation reaction was carried out at a constant temperature of 50°C, a stirring speed of 500 rpm, a pH value of 12.3, and a reaction time of 10 h to form precursor particles. 2.1 g of Ni 0.25 Mn0.75 The (OH)2 precursor was mixed with 1.4 g of Li2CO3, and the evenly dispersed solid phase powder was heated to 450°C at a heating rate of 5°C / min in an air atmosphere in a muffle furnace and kept warm for 6 hours. It was then heated to 850°C and sintered at high temperature for 12 hours. It was then naturally cooled to room temperature and ground and crushed to obtain a lithium-rich positive electrode material.
[0089] Comparative Example 1
[0090] On the basis of Example 1, the oxygen partial pressure was changed to 0%, and the other conditions remained unchanged.
[0091] Comparative Example 2
[0092] On the basis of Example 1, the oxygen partial pressure was changed to 100%, and the other conditions remained unchanged.
[0093] Structural characterization
[0094] From XRD Figures 1 to 3 It can be obtained that the diffraction peak is basically consistent with the standard card of lithium-rich materials, and in the range of 20° to 25°, the existence of superlattice peaks can be observed. The XRD spectrum shows a two-phase structure of LiMO2 layered phase and Li2MnO3 monoclinic phase.
[0095] When the oxygen partial pressure in the reaction system changes, it will affect the composition and structure of the precursor during the formation process. Specifically, a suitable oxygen partial pressure helps to form a precursor with an orderly structure and a single crystal phase. It has a great impact on the structural order and morphology of the subsequent positive electrode material. The separation of the diffraction peaks (108) / (110) of lithium-rich materials is a characteristic that reflects the quality of the material's layered structure. The more obvious the separation, the better the material's layered structure. Figures 1 to 3 It can be seen that the separation degree of the (108) / (110) peak becomes more obvious with the increase of oxygen partial pressure. When the oxygen partial pressure is too low, the layered structure formed by the material is poor. The layered structure of Example 1 is the best.
[0096] Electrochemical performance test
[0097] Test method: First, mix the prepared lithium-rich positive electrode material with Super P and PVDF in a mass ratio of 7:2:1. After sufficient grinding, add an appropriate amount of N-methyl-di-ethylpyrrolidone as a solvent, mix to form a uniform slurry, apply it on the surface of the aluminum foil, and dry it. Secondly, after the slurry is completely dry, cut the aluminum foil into round pieces (Φ=11mm), and weigh and record the mass. Finally, assemble the pole pieces in the order of positive electrode shell, pole piece, diaphragm, lithium sheet, gasket, shrapnel and negative electrode shell to form a button battery. The charge and discharge test was completed in the blue electric test system at room temperature and a voltage range of 2.0V to 4.8V. The test results are as follows Figures 4 to 11 shown.
[0098] Depend on Figure 4 It can be obtained that the first cycle charge and discharge curve shows the typical characteristics of the lithium-rich manganese-based positive electrode material prepared in Example 1. Its charging capacity consists of two significant areas: a slope area and a platform area at 4.5V. Specifically, in the slope area where the voltage is lower than 4.5V, the redox reaction of transition metal ions mainly occurs during the charging process. This reaction is similar to the cationic redox reaction of classical layered materials and is an important component of the charging performance of the material. When the voltage climbs to 4.5V and above, an obvious long platform appears on the curve. This platform area corresponds to the anionic redox reaction unique to lithium-rich materials, which completes the charge compensation process. It is this unique reaction mechanism that makes the lithium-rich material exhibit an impressive high specific capacity characteristic. The first cycle charge and discharge curve not only highlights the typical characteristics of lithium-rich manganese-based positive electrode materials, but also clearly reveals the key reactions and excellent performance in its charging process.
[0099] Figures 5 to 11 The cycle curves of the lithium-rich manganese-based positive electrode materials prepared in Examples 1 to 5 and Comparative Examples 1 to 2 are shown respectively. Figures 5 to 9 It can be obtained that the materials prepared in Examples 1 to 5 have good cycle performance, specifically, after 100 cycles of charge and discharge, the capacity retention rates are as high as 96.34%, 85.05%, 94.05%, 90.12%, and 84.42%, which also show better cycle performance. The advantage of suitable oxygen partial pressure can achieve effective pinning of transition metal ions in the Li layer. This unique mortise and tenon structure not only enhances the stability of the material structure to avoid the formation of unfavorable reduced or oxidized compounds of metal ions. Through the pinning mechanism, the migration and release of oxygen atoms can be limited, thereby improving the safety and stability of the material. The irreversible phase change of lithium-rich positive electrode materials during the charge and discharge process and the release of oxygen are suppressed.
[0100] Depend on Fig.10 It can be seen that the material prepared in Comparative Example 1 showed severe capacity decay during the cycle process, and the capacity retention rate after 100 cycles was only 82.1%, and the material's cycle and structural stability were poor. This is because in a low oxygen partial pressure environment, metal ions are more likely to form reduced compounds, which will cause changes in the element ratio, valence state, and microstructure in the precursor.
[0101] Depend on Fig.11 It can be seen that the material in Comparative Example 2 also showed serious capacity decay during the cycle process. After 100 cycles, the capacity retention rate was only 82.05%, and the material's cycle and structural stability were poor. This is because under high oxygen partial pressure conditions, metal ions are more easily oxidized to form high-valent ions or compounds. This will cause the chemical composition of the precursor to deviate from expectations and even form undesirable impurity phases.
[0102] Therefore, in order to prepare materials with excellent electrochemical properties and cycle stability, we need to strictly control the oxygen partial pressure conditions during the preparation process, so as to achieve effective pinning of transition metal ions in the Li layer. This unique mortise and tenon structure not only enhances the stability of the material structure, but also inhibits the irreversible phase change of lithium-rich cathode materials during the charge and discharge process and the release of oxygen, so as to ensure that the material has the expected electrochemical properties and stability.
Claims
1. A method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure, characterized in that: The following steps are involved: (1) introducing a nickel-manganese-based mixed sulfate solution and a complexing agent to obtain a solution A and a precipitant solution B into a reaction vessel, respectively, and adjusting the oxygen partial pressure in the reaction system to a predetermined range by controlling the ratio of oxygen and non-oxidizing gas; (2) performing a coprecipitation reaction to uniformly precipitate metal ions under a controlled oxygen partial pressure environment to form a coprecipitation product; (3) Separating the coprecipitated product, washing and drying it, the obtained hydroxide precursor Ni x Mn y M z (OH)2; (4) The hydroxide precursor and the lithium source are mixed and ground, and a lithium-rich manganese-based positive electrode material Li is prepared by solid-phase sintering or molten salt method. 1+a [Ni k Mn d M c ]O 2。 2. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The oxygen partial pressure is 10-60%.
3. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The Ni x Mn y M z In (OH)2, 0.2≤x≤0.26, 0.75≤y≤0.8, 0≤z≤0.06, and M is selected from Mg, Al, Ti, Zr, Nb, Mo, Fe, Zn, Na, W, Co, Cr, Y or Cu.
4. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The Li 1+a [Ni k Mn d M c ]O2, 0.08≤a≤0.26, 0.10≤k≤0.22, 0.45≤d≤0.66, 0≤c≤0.05, and M is selected from Mg, Al, Ti, Zr, Nb, Mo, Fe, Zn, Na, W, Co, Cr, Y or Cu.
5. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: In step (1), the concentration of the nickel-manganese-based mixed sulfate solution is 0.25-5 mol / L.
6. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The complexing agent in step (1) is ammonia water or oxalic acid.
7. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: In step (2), the precipitation reaction temperature is 30 to 80° C., and the reaction time is 8 to 20 hours.
8. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The precipitant is NaOH, and the pH of the precipitation reaction is 8-14.
9. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: The lithium source is one or more of Li2CO3, LiOH, LiOH·H2O or LiNO3.
10. The method for preparing high-performance lithium-rich manganese-based positive electrode materials by controlling oxygen partial pressure according to claim 1, characterized in that: In step (4), the sintering conditions of the solid phase method are as follows: a pre-sintering temperature of 400-600° C. for 4-8 hours, and after pre-calcination or directly heating to 700-1000° C. for high-temperature sintering for 9-15 hours.